2012
DOI: 10.5897/ajb11.1378
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive potential of symbiotic bacteria and fungi from marine sponges

Abstract: Marine sponges are rich in microbial biota. In this study, totally four sponges namely Callyspongia diffusa, Hyattella Cribriformis, Sigmadocia carnosa, Spongia officininalis Var ceylonensis were collected and their associated bacteria and fungi were isolated. Among the microbes isolated, Pseudomonas fluorescens and Penicillium citrinum were isolated from C. diffusa which showed broad range of activity against tested pathogens. This study demonstrates that the culturable fraction of bacteria and fungi from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Marine-derived fungi can be defined as microorganisms that live in colonies or a collection of microorganisms in the tissues of organisms or living things from the marine. They produce bioactive compounds developed as drugs [18], [19]. Several symbiotic fungi from marine biota had been reported to be developed as antidiabetic drugs [20].…”
Section: Resultsmentioning
confidence: 99%
“…Marine-derived fungi can be defined as microorganisms that live in colonies or a collection of microorganisms in the tissues of organisms or living things from the marine. They produce bioactive compounds developed as drugs [18], [19]. Several symbiotic fungi from marine biota had been reported to be developed as antidiabetic drugs [20].…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our findings, Shen et al 32 reported the antimicrobial activity of marine-derived Penicillium oxalicum strain O312F crude extract, which displayed strong antifungal activity against A. brassicicola and F. graminearum. In addition, the antifungal activity of Penicillium citrinum isolated from a marine sponge, Callyspongia diffusa, collected in the Gulf of Mannar, on the southeast coast of India 45 . Penicillium citrinum crude extract also displayed strong antifungal activity against nine plant pathogenic fungi, including Alternaria alternata, Botrytis cinerea, Cercospora theae, Fusarium udum, F. oxysporum, Macrophomina phaseolina, Poria hypolateritia, Phomopsis thae and R. solani.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has emerged, demonstrating that many natural products extracted from marine animals and algae are the products of associated microorganisms, mostly bacteria, and fungi (Raghukumar 2008). Spongeassociated fungi have the potential to produce new chemical entities (Volgraf et al 2008;Blunt et al 2010;Vasanthabharathi 2012;Vicente et al 2013;Bolanos et al 2015;Imhoff 2016;Indraningrat et al 2016) that actively inhibited the growths of various pathogenic microorganisms (Khoeri et al 2011;Mayer et al 2013;Radjasa et al 2013;Buttachon et al 2016;Corral et al 2018). Our previous research also showed that spongeassociated fungi have several bioactivities such as anti-S. aureus and E. coli (Wittriansyah et al 2016), antibacterial produced by sponge Agelas sp.…”
Section: Introductionmentioning
confidence: 97%